Underdiagnosis of Metabolic Syndrome in Non-Hispanic Black Adolescents: A Call for Ethnic-Specific Criteria - DeBoer, Mark D. (2010)
Childhood obesity is a risk factor for the development of both type 2 diabetes mellitus (T2DM) and cardiovascular disease (CVD). One marker that can be used to predict T2DM is the metabolic syndrome (MetS). MetS, a cluster of cardiovascular factors associated with insulin resistance, is defined by central obesity, impaired fasting glucose, hypertension, elevated triglycerides (TG), and low levels of high-density lipoprotein cholesterol. Some have advocated using a diagnosis of MetS to trigger increased intervention in children. However, ethnic differences in MetS may hamper identification of at-risk children. For example, non-Hispanic blacks are diagnosed with MetS less frequently than non-Hispanic whites, despite having higher rates of T2DM and CVD. These differences in MetS are predominantly due to a low frequency of hypertriglyceridemia in non-Hispanic blacks. Compared with non-Hispanic whites and Mexican Americans, non-Hispanic blacks have lower TG levels at baseline but exhibit worsening insulin resistance with increasing TG. Therefore “normal” TG levels appear to be falsely reassuring among insulin-resistant non-Hispanic blacks. Ethnic-specific tools may be needed to more accurately predict risk for T2DM and CVD in minorities.